Catechol-O-methyltransferase (COMT) genotype affects cognitive control during total sleep deprivation. (February 2018) - Satterfield, Brieann C.; Hinson, John M.; Whitney, Paul; Schmidt, Michelle A.; Wisor, Jonathan P.; Van Dongen, Hans P.A.
Abstract: Adaptive decision making is profoundly impaired by total sleep deprivation (TSD). This suggests that TSD impacts fronto-striatal pathways involved in cognitive control, where dopamine is a key neuromodulator. In the prefrontal cortex (PFC), dopamine is catabolized by the enzyme catechol- O -methyltransferase (COMT). A functional polymorphism (Val158Met) influences COMT's enzymatic activity, resulting in markedly different levels of prefrontal dopamine. We investigated the effect of this polymorphism on adaptive decision making during TSD. Sixty-six healthy young adults participated in one of two in-laboratory studies. After a baseline day, subjects were randomized to either a TSD group ( n  = 32) with 38 h or 62 h of extended wakefulness or a well-rested control group ( n  = 34) with 10 h nighttime sleep opportunities. Subjects performed a go/no-go reversal learning (GNGr) task at well-rested baseline and again during TSD or equivalent control. During the task, subjects were required to learn stimulus–response relationships from accuracy feedback. The stimulus–response relationships were reversed halfway through the task, which required subjects to learn the new stimulus–response relationships from accuracy feedback. Performance on the GNGr task was quantified by discriminability ( d′) between go and no-go stimuli before and after the stimulus–response reversal. GNGr performance did not differ between COMT genotypes when subjects were well-rested. However, TSD exposed a significant vulnerability to adaptive decision making impairment in subjects with the Val allele. Our results indicate that sleep deprivation degrades cognitive control through a fronto-striatal, dopaminergic mechanism.